Brazilian catfish parasitized by Epistylis sp. (Ciliophora, Epistylididae), with description of parasite intensity score - De Pádua, Santiago Benites [UNESP]; Ishikawa, Márcia Mayumi; Ventura, Arlene Sobrinho; Jerônimo, Gabriela Tomas; Martins, Maurício Laterça; Tavares, Luiz Eduardo Roland (Springer Nature, 2013)
The determination of mean intensity of parasitism for colony-forming sessile protozoan such as Epistylis has been a great problem in parasitological studies. Some alternatives have been proposed by researchers for laboratory and field conditions. This study describes the criteria to establish the parasitic intensity score for epistylidid infestation in fish. Parasite distribution and the host-parasite relationship in four species of Brazilian cultured catfish and their hybrids are discussed. The highest prevalence rates were found in the hybrid jundiara, Leiarius marmoratus male × Pseudoplatystoma reticulatum female (96.4 %), followed by jurupoca, Hemisorubim platyrhynchos (60 %), and the hybrid surubim, Pseudoplatystoma corruscans male × P. reticulatum female (52.7 %). Positive correlation between parasitic intensity score and the fish size, weight, and relative condition factor were also observed. These findings indicate that Epistylis infestation in Brazilian catfish is an emerging disease in cultured fish. © 2012 Springer-Verlag.
Keywords: body surface; Brazil; catfish; ciliate infection; Epistylis infection; female; Hemisorubim platyrhynchos; host parasite interaction; Leiarius marmoratus; male; nonhuman; parasite load; priority journal; Pseudoplatystoma corruscans; Pseudoplatystoma reticulatum; scoring system; species distribution; Animals; Body Weight; Catfishes; Ciliophora Infections; Female; Fish Diseases; Male; Oligohymenophorea; Parasite Load; Ciliophora; Epistylis; Protozoa; Pseudoplatystoma